Early Stage Development Of Geography Modules Of Design-Based Planning In The Study Program Of Education Geography STKIP PGRI West Sumatera - Yusutria Yusutria; Nefilinda Nefilinda (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The purpose of this research is to develop a faith-based disaster geography module. The module is one source of learning for students, which can facilitate students to get information and easy to apply to the public, so it can be instrumental in facing disaster. The development study used a 4D model involving three steps namely: define, design, and develop. The instruments used are validation, activities and interviews. The define phase showed that the geography lecture material of disaster is in conformity with the standards of competence and achievement lecture. The results showed that the design module validation is valid enough according to the criteria and many improvements. However, the results described here is an initial validation, and therefore still need to be validated by disaster experts, educational experts and Indonesian language experts.